Analisis Keakuratan Terjemahan Tindak Tutur Direktif Dalam “Subtitle” Dialog Film The Mask Of Zorro - Lenny Brida; Mawarta Onida Sinaga (Epigram, 2019)
This research is a study of the quality of the translation of directive speech acts in the subtitle of The Mask of Zorro. There are four objectives achieved from this research, namely; 1) identify the types of directive speech acts used in the subtitle of the film dialogue The Mask of Zorro, 2) describe the types of speech acts used at different social strata. 3) describe the techniques used in translating directive speech acts 4). accessing the accuracy of the translation results. The results of the study explained four findings. The first finding shows that the most used directive speech acts category is Requirements (39%), namely instructing explicitly, ordering, wanting, demanding. the second category is Requestives (35%) which is used to invite, ask, beg, and invite food. While the speech acts of advices (advices) only (11%) are encouraging, advising, warning, suggesting.